Discovering IoT implications in business and management: A computational thematic analysis. (December 2022) - Delgosha, Mohammad Soltani; Hajiheydari, Nastaran; Talafidaryani, Mojtaba
Abstract: IoT as a disruptive technology is contributing toward ground-breaking experiences in contemporary enterprises and in our daily life. Rapidly changing business environment and phenomenally evolving technology enhancement necessitate a robust understanding of IoT implications from business and management perspective. The current study benefits from an explanatory sequential mixed-method approach to represent and interpret the inductive topical framework of IoT literature in business and management with emphasis on business model. Bayesian statistical topic model called latent Dirichlet allocation is employed to conduct a comprehensive analysis of 347 related scholarly articles to reveal the topical composition of related research. Further, we followed a thematic analysis for interpreting the extracted topics and gaining in-depth qualitative insights. Theoretical implications with emphasizing on research agenda for future study avenues and managerial implications based on influential themes are provided. Highlights: This study sheds light on the topical structure of IoT research in Business and Management context. Following explanatory sequential mixed-method, it represents and analyses 10 identical topics from 347 scholarly articles. This paper investigates the temporal trend of topics to display the hot and cold research topics' distribution over time. IoT-enabled Business Model is the highly attracted topic, so its latent topics are rendered to enrich our understanding. By presenting the research gaps, this paper proposes the future avenues of IoT studies in Business and Management.